Genetic variant of TGF-ß associated with decreased renal function in type II diabetes mellitus patient: single center pilot study in Indonesia - Anggelia Puspasari; Elfiani Elfiani; Susan Tarawifa; Rina Nofri Enis; Asro Hayani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The interaction between genetic factors, blood glucose and hypertension plays a role in the onset of diabetic kidney disease (DKD) in type II diabetes mellitus (T2DM). Genetic variation of TGF-ß1 is associated with renal complication in T2DM with varying results between ethnicities. The Jambi Malay ethnic, which is the majority ethnic in Jambi Province, is an area that reports an increased prevalence of T2DM with DKD as the most frequent microvascular complications. In addition, previous study reported controlling blood glucose not associated with DKD indicating genetic may have play a role in DKD in this population. Studies related to genetic variation and decreased kidney function in T2DM patients has never been performed in this ethnic group. This study aimed to investigate the role of TGF-ß genetic variation as risk factor for decreased renal function in T2DM patients from Jambi Malay ethnicity. We conducted a cross sectional study involving 70 patients with T2DM. The inclusion criteria for renal complication based on a decrease in the glomerular filtration rate (GFR) of less than 60 mL/min/1.73. The genotyping method used was amplification refractory mutation system polymerase chain reaction (ARMS-PCR) for TGF-β1 rs1800470 T/C. Bivariate and multivariate analysis was performed to analyze phenotype and genotype association. The result of bivariate analysis showed T2DM patients with genotype CT (p:0.006; OR:0.125; 95% CI:0.027-0.575) and CC (p:0.007; OR:0.104; 95% CI:0.020-0.546) or C allele carrier (p:0.003; OR:0.117; 95% CI:0.027-0.500) had lower risk for decreased renal function than TT genotype. Multivariate analysis that included blood pressure and age variables showed the same finding for CT (p:0.007; OR:0.086; 95% CI:0.014-0.508) and CC genotype (p:0.022; OR:0.115; 95% CI:0.018-0.731). It is concluded from this study that T2DM patients with genotype CT, CC and carrier allele C have a lower risk for suffering kidney complications than genotype TT.